ANALISIS KINERJA MOTOR INDUKSI 3 FASA DARI ASPEK BESARAN DAYA DAN EFISIENSI MOTOR DALAM MENGGERAKKAN MESIN (STUDI KASUS PADA MESIN JAW CRUSHER DI PT. ALAM TUNGGAL SEMESTA) - Rayhan Pramana Rizqi, Muhammad (Universitas Lampung, 2024)
Stone crushing in the construction world for the needs of split stone requires a tool called Crusher, one type that is quite often used is Jaw Crusher. The Jaw Crusher at PT Alam Tunggal Semesta uses a 3 Phase Induction motor as its drive. However, induction motors also have several problems related to power, efficiency, and torque that need to be considered. Where the 3-phase induction motor can be calculated the amount of power and efficiency in order to determine the performance of the induction motor. The results of the calculation analysis of the efficiency and power when the motor is starting obtained a motor efficiency of 8.72% - 31.85% and at the highest power of 73KW, so that the motor efficiency when starting is still below the nominal value of the motor which is 92% and for the power exceeds the nominal value of the motor which is 37KW. When the motor is no load, the calculated efficiency is 82-99% or an average of 92.75% is obtained and the power is 8.49-9.74KW, so the motor efficiency when there is no load is in accordance with the nominal value of the motor and the power is below the nominal power of the motor. When there is a load, the motor efficiency calculation is 48-98% or an average of 78.07% is obtained and the power is 6.8-10KW, which indicates that when the motor has a load, the efficiency obtained is below the nominal value of the motor and the power is still below the nominal power of the motor